Rancangan Aplikasi Pengolahan Data Alumni MTS Swasta Citra Amanah Berbasis Web - Pramudya Pramudya; Sondang Sondang (JOURNAL SAINS STUDENT RESEARCH, 2026)
The advancement of information technology has prompted educational institutions to manage data more effectively and efficiently. MTs Swasta Citra Amanah still faces challenges in managing alumni data, which has been done manually, often leading to issues such as unstructured data, difficulties in information retrieval, and suboptimal reporting processes. To address these problems, a Web-Based Alumni Data Processing Application Design was developed. This system was built using the PHP programming language and MySQL database, employing the waterfall development method. The results of the study indicate that the system is capable of processing alumni data in a computerized manner, providing faster and more accurate search and reporting features, and improving the effectiveness of information management. With this system, the school can conduct alumni data collection in a more structured, transparent, and easily accessible manner at any time.